An extended european foundation for quality management excellence model for quality performance in Malaysian higher education institutions - Ismail, Rosli (2016)
In the recent years, Information Systems (IS) have significantly impacted most organizations and they were widely researched. Subsequently, it is obvious that using IS influences all components, functions and activities of an organization. In Europe, The European Foundation for Quality Management (EFQM) excellence model was introduced at the beginning of 1992 as the framework for assessing organizations for the European Quality Award. In fact, this model has been claimed to be the most widely used model of the national excellence awards in the European countries. However, despite the supportive role of IS in quality management, it does not exist in EFQM excellence model as an individual criterion. Hence, this study aimed to extend the EFQM excellence model by integrating the model with Measurement, Analysis and Knowledge Management; and Student, Stakeholder and Market focus factors in Malcolm Baldrige National Quality Award (MBNQA) model to make it more useful and contributory for an implementation in Malaysian Higher Educational Institutions (HEIs). Therefore, the study posed several objectives as follows: Firstly, the study proposed an extended EFQM excellence model by integrating the EFQM excellence model and MBNQA model. Secondly, the study was carried out to evaluate the interrelationships among the extended EFQM excellence model criteria in the Malaysian HEIs. Thirdly, this study was done to determine the effects of information systems on the extended EFQM excellence model in the HEIs of Malaysia. The extended EFQM excellence model comprised of 11 criteria which included leadership; policy and strategy; people; partnership and resources; student, stakeholder and market focus; measurement, analysis and knowledge management; processes; people results; customer results; society results; and key performance results. Based on the extended EFQM excellence model, twenty four (24) hypotheses were developed and statistically tested. The study used cross-sectional survey methodology. The samples were drawn from Malaysian HEIs based on the directory in the Ministry of Higher Education (MOHE) of Malaysia’s website. The final number of respondents involved in this study was 118 HEIs. The data of the study were analysed by applying Structural Equation Model (SEM). In brief, the results supported twenty (20) hypotheses while four (4) hypotheses were not supported. And, also, the data supported the impacts of IS on several criteria of the extended EFQM excellence model and this evidenced that both EFQM criteria and IS criterion should be implemented holistically, rather than piecemeal. Finally, an acceptable level of fitness was achieved. When the fitness of the model is acceptable, it is concluded that not only the theory of EFQM excellence model are supported by the data, but also the integration of the EFQM excellence model with IS has successfully been conducted.